New Networks, Competition and Regulation - Pio Baake; Ulrich Kameckey (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
We consider a model with two firms operating their individual networks. Each firm can choose its price as well as its investment to build up its network. Assuming a skewed distribution of consumers, our model leads to an asymmetric market structure with one firm choosing higher investments. While access regulation imposed on the dominant firm leads to lower prices, positive welfare effects are diminished by strategic investment decisions of the firms. Within a dynamic game with indirect network effects leading to potentially increased demand, regulation can substantially lower aggregate social welfare. Conditional access holidays can alleviate regulatory failure.
Keywords: L51; D43; L13; 330; Regulation; network effects; natural monopoly; Stromnetz; Netzzugang; Elektrizitätswirtschaft; Regulierung; Niederlande; EU-Staaten; Großbritannien; Neuseeland